Inovasi Pelayanan Publik pada Pemerintah Daerah - Kaka, Ekson; Widyani, Ida Ayu Putu Sri (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This research is motivated by the demands of society regarding public services and the need for innovation in public services, both carried out by the government and other components of society. This research aims to determine service innovations carried out in NTB Province, especially service innovations in several sub-district local governments in West Nusa Tenggara, namely Mataram District, Sekar Beli District,. Next, to determine the inhibiting factors in implementing public service innovation in West Nusa Tenggara. The research method used is a qualitative method with a descriptive approach. The key informants in this research were Mataram District, Sekar Beli District and Sandu Baya District. The results show that Bawasanya innovation services have been carried out in several sub-districts such as PATEN on The Road, Zero Compliant, Gerimis Senja (poverty alleviation movement), android information via online about land information. But there is still low equality in various community service innovation programs in reducing poverty to date. So the government needs to be reviewed and re-evaluated so that the service innovation program created can reach the masses. So that the public feels equal distribution of public service innovation.